Seed vigor and initial growth of coriander, rupincin and parsley seedlings with different fertilizations - José Smiderle , Oscar; das Graças Souza, Aline (Seven Editora, 2023)
Coriander vegetables (Coriandrum sativum L.), arugula (Eruca sativa Mill.) and parsley (Petroselinum sativum Hoffm.) are important as healthier food sources. Coriander belongs to the Apiaceae family and is widely used in Brazilian cuisine, mainly leaves and branches. Parsley is a condiment originating in Europe and the arugula is rich in mineral salts and vitamins A and C, appreciated for its spicy taste and pleasant and pronounced smell. Demand for vegetables has increased in recent years, and it is necessary to seek ways to increase agricultural production. The objective of this work was to determine germination,  seed vigor and initial growth of coriander, arugula and parsley seedlings. The experiments were carried out at the Seed AnalysisLaboratory and greenhouse of Embrapa Roraima. Seeds of lots of vegetables were characterized. Germination test in two lots of parsley, after 24 immersion in water in two environments. Electrical conductivity test of seeds with readings in 3, 6, 9, 12 and 24 hours of immersion. In greenhouse seeds of the three vegetables in trays with sand to evaluate the emergence. The average mass data of 100 parsley seeds obtained were between 0.018 g and 0.019 g, arugula 0.022 g and coriander 0.16 g. In an experiment to evaluate the germination of parsley seeds in two environments at seven days, it was obtained: germination of seeds of lot 1 in environment 1 was 68% and in environment 2 of 78%, for lot 2 in environment 1 was 75% and in environment 2 of 78%. For the control, germination of 53% was found in environment 1 and 75% in environment 2. Immersion in water for 24 hours increased the germination of parsley seeds. At14 days, lot 1 presented 52.1% of seeds with radicle greater than 1.5 cm at 23ºC and 54.2% at 28ºC. For lot 2 it was 52.1% and 57.1% in these environments. Immersion increased radicle vigor in relation to the control (19.2% and 29.8%) for temperatures of 23ºC and 28ºC, respectively. The values obtained for electrical conductivity in coriander seeds were 184.3 μS cm-1 g-1, for arugula 127.4 μS cm-1 g-1 and 498.2 μS cm-1 g-1 for parsley. The germination percentages of these seeds were 69%, 86%, 80% for coriander, arugula and parsley, respectively. In the germination in sand determined at 12 days it was verified for coriander 34%, of the arugula 59% and of the parsley 53%. The immersion of parsley seeds in water for 24 hours before germination increases germination and increases seedling vigor. In a greenhouse environment, the germination of vegetables behaved differently to the laboratory. DOI: https://doi.org/10.56238/tfisdwv1-113